2013
DOI: 10.1186/1471-2393-13-59
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and risk factors for perineal trauma: a prospective observational study

Abstract: BackgroundOur aim was to describe the range of perineal trauma in women with a singleton vaginal birth and estimate the effect of maternal and obstetric characteristics on the incidence of perineal tears.MethodsWe conducted a prospective observational study on all women with a planned singleton vaginal delivery between May and September 2006 in one obstetric unit, three freestanding midwifery-led units and home settings in South East England. Data on maternal and obstetric characteristics were collected prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
236
2
30

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(320 citation statements)
references
References 54 publications
23
236
2
30
Order By: Relevance
“…Consequently, our study has found evidence of the clear protective or preventive effect of episiotomy with respect to second degree tears for primiparous women. This association with a decreased risk of spontaneous perineal trauma was also evidenced in other studies (22,23). Potentially as much as 80% of the second degree tears in spontaneous deliveries could have been prevented or avoided if an episiotomy had been performed.…”
Section: Discussionsupporting
confidence: 52%
“…Consequently, our study has found evidence of the clear protective or preventive effect of episiotomy with respect to second degree tears for primiparous women. This association with a decreased risk of spontaneous perineal trauma was also evidenced in other studies (22,23). Potentially as much as 80% of the second degree tears in spontaneous deliveries could have been prevented or avoided if an episiotomy had been performed.…”
Section: Discussionsupporting
confidence: 52%
“…U většiny žen během porodu vzniká porodní poranění (1). Mezi nejčastější spontánní poranění patří ruptury hráze.…”
Section: Problém Literárního Přehledu Má Porodní Poranění Hráze (Sponunclassified
“…4. stupeň: ruptura zevního análního svěrače a vnitřní-ho análního svěrače a mukózy rekta. Dle studie autorů Smith et al (1), vznikají ruptury hráze 1. stupně u 5-18 % vaginálních porodů a ruptury 2. stupně u 20-38 % porodů. Rozsáhlé ruptury s poraněním análního sfinkteru postihují 1-4 % žen (5,6).…”
Section: Problém Literárního Přehledu Má Porodní Poranění Hráze (Sponunclassified
“…This is a common event that affects women across a variety of international settings (Barreto-Scarabotto and Gonzalez-Riesco, 2008;Kettel et al, 2010;Ismail et al, 2013;Smith et al, 2013). Despite the frequency of the event there is a dearth of research which relates to women's experience of perineal suturing or the clinician's decision to suture.…”
Section: To Pain Associated With Suturing Second Degree Perineal Tearmentioning
confidence: 99%